Superiority of continuous over intermittent intraoperative nerve monitoring in preventing vocal cord palsy. Issue 5 (26th May 2021) - Schneider, R; Machens, A; Sekulla, C; Lorenz, K; Elwerr, M; Dralle, H
Abstract: Background: Continuous intraoperative nerve stimulation (IONM) with uninterrupted monitoring is likely better than intermittent IONM in preventing vocal cord palsy after thyroid surgery. Methods: This was a comparative study of intermittent versus continuous IONM in patients with benign and malignant thyroid disease treated at a tertiary centre over 10 years. Early postoperative and permanent vocal cord palsy rates were estimated. Multivariable logistic regression analysis was used to quantify the contributions of clinical and histopathological variables to early postoperative and permanent vocal cord palsy. Results: A total of 6029 patients were included, of whom 3139 underwent continuous and 2890 intermittent IONM. Based on nerves at risk (5208 versus 5024 nerves), continuous IONM had a 1·7‐fold lower early postoperative vocal cord palsy rate than intermittent monitoring (1·5 versus 2·5 per cent). This translated into a 30‐fold lower permanent vocal cord palsy rate (0·02 versus 0·6 per cent). In multivariable logistic regression analysis, continuous IONM independently reduced early postoperative vocal cord palsy 1·8‐fold (odds ratio (OR) 0·56) and permanent vocal cord palsy 29·4‐fold (OR 0·034) compared with intermittent IONM. One permanent vocal cord palsy per 75·0 early vocal cord palsies was observed with continuous IONM, compared with one per 4·2 after intermittent IONM. Early postoperative vocal cord palsies were 17·9‐fold less likely to become permanent with continuous than intermittent IONM. Conclusion: Continuous IONM is superior to intermittent IONM in preventing vocal cord palsy.